Development and delivery of occupational health and safety management program through open and flexible distance learning - Suhaila Abdul Hamid; Norlia Goolamally; Mansor Fadzil (2013)
Open and flexible distance education (OFDE) removes the barriers to quality post-secondary distance education by offering quality programme through flexible delivery system with minimum admission requirements. OFDE also provides opportunity for working adults to seek lifelong education in a flexible manner. In line with the Occupational Safety and Health Master Plan for Malaysia 2015 (OSH-MP 15), Open University Malaysia (OUM) has been on the forefront in spearheading effort to offer Bachelor of Occupational Health and Safety Management (BOHSM) with honours and Master of OSH Risk Management (MOSHRM) through OFDE. Although it is quite challenging to offer science and technical related subjects through open and flexible distance learning, OUM has taken a bold step to explore the possibilities. This paper aims to present Open University Malaysia’s experience in the development and delivery of the BOHSM with Honours and MOSHRM through open and flexible distance learning. This paper will share the strategies adopted by OUM. (Abstract by authors)